Polymorphism of the TMPRSS2 gene relating to COVID-19 subceptibility in Vietnamese population - Ton, Nguyen Dang; Nhung, Vu Phuong; Trang, Duong Thu; Hoa, Nguyen Thi Thanh; Nam, Nguyen Hoai; Thuan, Hoang Thi; Son, Ho Anh; Hai, Nguyen Thi Thanh; Thach, Pham Ngoc; Hai, Nong Van; et al. (Academia Journal of Biology, 2021)
Recently, a contagious lung disease named coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rapidly spread worldwide and has many serious consequences for human health. Human genetic polymorphisms may contribute to the variation of incidence, mortality as well as severity of COVID-19. To date, this factor in the Vietnamese population remains unknown. A cellular protease termed transmembrane protease serine 2 (TMPRSS2) was found to play a vital role in the entry of SARS-CoV-2 into host cells. In this study, we investigated polymorphisms in the TMPRSS2 gene from 270 whole exome sequencing data of Vietnamese peoples. We also employed bioinformatics tools including SIFT, Polyphen-2, and PROVEAN to predict the possible function of missense variants. A total of 34 TMPRSS2 variants were identified, of which, 29 were in non-coding regions and 14 were in coding regions. Variants found in exons included seven synonymous and seven non-synonymous point mutations, one of which was novel mutation (c.A1336C/p.R446R). Mutation c.G589A/p.V197M (rs12329760) possesses the highest frequency and was predicted to have the ability to damage protein by SIFT and Polyphen-2. In addition, the damaging possibility was also found in c.T244G/p.Y82D and c.C896T/p.A299V variants. This study contributes to the understanding of Vietnamese genetic variation databases relating to susceptibility to COVID-19.